OPTIMASI DAN SIMULASI SISTEM PENYEDIAAN JARINGAN AIR BERSIH DI KECAMATAN KADEMANGAN KABUPATEN BLITAR - Lufira, Rahmah Dara; Suhardjono, Suhardjono; Marsudi, Suwanto (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2012)
The purpose of this study was to determine how the effects in terms of technical and economic optimization if done the pipe and the pump head and the simulation of water pricing on water supply systems network in the Kademangan District Blitar Regency. While the purpose of this study contribute ideas to the relevant agencies so that it can be used as a reference whether for optimization and simulation of network systems providing clean water, decent built or not.The method used in this study is the analysis of water network with watercad software in order to obtain the total project cost incurred economic analysis was then performed to determine the magnitude of benefits that can be obtained after the project was built involved the comparison of Benefit Cost Ratio (B/C = 1), Net present Value (NPV), Internal Rate of Return (IRR), the breakeven point of investment and sensitivity analysis can then be used as the basis for tariff setting water prices.Based on the results of simulation and optimization of the selected alternatives are technically and economically feasible are alternative 2, which consists of GIP pipes with diameters ranging from 300 mm up to 2.54 km of water sources and PVC pipe 250 mm starting from the end of the pipe to the reservoir with GIP distance of 3.12 km. With a pump head of 130 m using a pump Grundfos SP 125 type 5A with a capacity of 25 l/s in 2 units. The total cost of investment needed to build a network of water supply system is Rp. 18,428,996,200 with the price of water that is suitable and economically viable is Rp. 10,500.Key Word: optimation, pipe system, simulation, alternative price of water